Engineering enzyme access tunnels - Kokkonen, Piia; Bednar, David; Pinto, Gaspar; Prokop, Zbynek; Damborsky, Jiri (Biotechnology advances, 2019)
Enzymes are efficient and specific catalysts for many essential reactions in biotechnological and pharmaceutical industries. Many times, the natural enzymes do not display the catalytic efficiency, stability or specificity required for these industrial processes. The current enzyme engineering methods offer solutions to this problem, but they mainly target the buried active site where the chemical reaction takes place. Despite being many times ignored, the tunnels and channels connecting the environment with the active site are equally important for the catalytic properties of enzymes. Changes in the enzymatic tunnels and channels affect enzyme activity, specificity, promiscuity, enantioselectivity and stability. This review provides an overview of the emerging field of enzyme access tunnel engineering with case studies describing design of all the aforementioned properties. The software tools for the analysis of geometry and function of the enzymatic tunnels and channels and for the rational design of tunnel modifications will also be discussed. The combination of new software tools and enzyme engineering strategies will provide enzymes with access tunnels and channels specifically tailored for individual industrial processes.
Keywords: Channel; Ligand binding; Pore; proteinové inženýrství; Protein engineering; Dynamics; biotechnologie; Pathway; Protein Engineering; Protein design; Software; Catalytic Domain; Biotechnology; Tunnel; Catalysis; software; Product release; katalytická doména; katalýza; Substrate entry